Pregnant Women’s Complience in Preventing Mother to Child Transmission (PMTCT) Examination - Ulfa, Maria; Monica, Laily Prima; Wulandari, Ratna Feti (Journal of Ners and Midwifery, 2024)
HIV infection during pregnancy not only threatens the health and safety of the mother, but can also pose a threat to the fetus. This is because pregnant women with HIV infection have a high risk of mother to child transmission (MTCT) or vertical transmission from mother to baby. This research was a descriptive study which aimed to see the compliance of pregnant women in PMTCT examinations. The population in this study was all pregnant women in the Sutojayan Community Health Center working area who had not taken a PMTCT examination. The sample in this study was 20 pregnant women who had not taken a PMTCT examination at the Sutojayan Community Health Center. The sampling technique used Accidental sampling. Inclusion criteria in this study include (1) pregnant women who had not taken a PMTCT examination, (2) being able to read and write. The instrument in this study used a questionnaire sheet containing compliance statements related to the PMTCT examination developed by the researcher. The data analysis method was by using a frequency distribution. This study was carried out from 10 to 19 April 2023. The results of this study showed that the majority of respondents in the compliant category in the PMTCT examination were 14 respondents (70%) and the number of respondents in the non-compliant category in the PMTCT examination was 6 respondents (30%). PMTCT examination is very important for pregnant women to reduce the risk of HIV transmission from mother to child.